Hubungan antara Keikhlasan dan Kematangan Emosi dengan Postpartum Depression pada Ibu Primipara - Aqila, Afza; Dinni, Siti Muthia (Universitas Islam Indonesia, 2022)
Serving out of post-natal care role is not an easy thing, especially for mothers who are giving birth to children for the first time. The adaptation process to become a primiparous mother have some problems, one of them is that it can cause Postpartum Depression (PPD). In addition, the things which are suspected to be causes of PPD are their spiritual factor which is sincerity and their psychological factor which is emotional maturity. This study aims to find out the relationship of sincerity and self-emotional maturity with postpartum depression in primiparous mothers. The subjects of the study were 110 primiparous mothers. Data analysis used in this study was the quantitative approach. Data collection methods used were the scale of sincerity, the scale of emotional maturity, the scale of postpartum depression. Data analysis of the study used IBM SPSS 22.0 program for windows. The result of the study showed that there was a relationship of sincerity and emotional maturity with postpartum depression in primiparous mothers (r = .405, p < .01), it means the higher level of sincerity and emotional maturity, the lower risk of postpartum depression, and vice versa. There was no significant relationship of sincerity with postpartum depression (r = -.136, p > .01). There was a very significant negative relationship of emotional maturity with postpartum depression (r = -.266, p < .01). The results of this study implied the importance of doing an assessment related to mother’s sincerity and her emotional maturation before a mother gives birth to her first child and conduct the education related to this.